Metal Nanoparticles Incorporated within Graphene-Enzyme Preparations for Synergistic Multiactive Catalysts - Noelia Losada-Garcia (10014995); Esteban P. Urriolabeitia (1670488); Jose M. Palomo (10015001) (1753)
The development of catalytic systems with different chemo- and biocatalytic functionalities for sustainable one-pot multistep transformations represents a big challenge in modern chemistry. Here, we have designed and synthesized enzyme-metal hybrids’ materials of palladium and copper as multiactive heterogeneous catalysts. The in situ formation of metallic nanoparticles of different size and species on multilayer graphene-anchored Candida antarctica lipase (G@CALB) at room temperature and aqueous media allowed creation of different kinds of enzyme-metal nanoarchitectures, where the metal nanoparticles were synthesized exclusively when induced by an enzyme, dispersed homogeneously on the enzyme structure as the scaffold. The creation of copper or palladium nanoparticles on the graphene-enzyme preparation allowed obtaining a new type of enzyme-metal bifunctional catalyst conserving the enzymatic activity intact and enhancing the metallic properties. Furthermore, the creation of a CuPd alloy on immobilized enzyme preparation (G@CALB-PdNPs-CuNPs) allowed obtaining a new enzyme-bimetallic trifunctional catalyst, with extremely enhanced metallic activity by the synergistic effect. These hybrids were successfully applied in different cascade processes, where the hybrid G@CALB-PdNPs-CuNPs , based on its property, showed superior efficiency to bifunctional hybrids in the regioselective and asymmetric one-pot tandem processes tested.